Inducible Nitric Oxide Synthase Inhibition in the Medial Prefrontal Cortex Attenuates the Anxiogenic-Like Effect of Acute Restraint Stress via CB1 Receptors - Coelho, Arthur A.; Vila-Verde, Carla; Sartim, Ariandra G.; Uliana, Daniela L.; Braga, Laura A.; Guimarães, Francisco S.; Lisboa, Sabrina F. (Frontiers in Psychiatry, 2022)
Stress exposure can result in several proinflammatory alterations in the brain, including overexpression of the inducible isoform of nitric oxide synthase (iNOS) in the medial prefrontal cortex (mPFC). These changes may be involved in the development of many psychiatric conditions. However, it is unknown if iNOS in mPFC plays a significant role in stress-induced behavioral changes. The endocannabinoid (ECB) system is also influenced by stress. Its activation seems to be a counterregulatory mechanism to prevent or decrease the stress-mediated neuroinflammatory consequences. However, it is unclear if the ECB system and iNOS interact to influence stress consequences. This study aimed to test the hypothesis that the anti-stress effect of iNOS inhibition in mPFC involves the local ECB system, particularly the CB1 cannabinoid receptors. Male Wistar rats with guide cannula aimed at the mPFC were submitted to acute restraint stress (RS) for two hours. In the following morning, rats received bilateral microinjections of vehicle, AM251 (CB1 antagonist; 100 pmol) and/or 1400W (iNOS selective inhibitor; 10-4, 10-3 or 10-2 nmol) into the prelimbic area of mPFC (PL-mPFC) before being tested in the elevated plus-maze (EPM). iNOS inhibition by 1400W prevented the anxiogenic-like effect observed in animals submitted to RS. The drug did not promote behavior changes in naive animals, demonstrating a stress-dependent effect. The 1400W-anti-stress effect was prevented by local pretreatment with AM251. Our data suggest that iNOS inhibition may facilitate the local endocannabinoid signaling, attenuating stress effects.